Association of Adiponectin with Lung Function Impairment and Disease Severity in Chronic Obstructive Pulmonary Disease - Jaswal, Shivani (Int J Appl Basic Med Res, 2018)
CONTEXT: Chronic obstructive pulmonary disease (COPD) is not only restricted to the pulmonary inflammation and airway obstruction but is also associated with comorbidities, which affect the therapeutic intervention and the quality of life and survival. Markers that can predict the systemic inflammation and a decline in the pulmonary function are of scientific interest. Adiponectin (APN) appears to be one such biomarker and can be used as a potential indicator of severity and response to treatment in patients of COPD. AIMS: The study aims to find out the role of APN as a marker of inflammation in the pathogenesis of COPD and explore its relationship with the severity of the disease. SETTINGS AND DESIGN: This was a cross-sectional study. SUBJECTS AND METHODS: The study group consisted of 60 patients of COPD, which included 30 males admitted with acute exacerbation of COPD (AECOPD) and 30 males with stable COPD. The study group was compared with 30 healthy, age-matched males. APN was estimated by commercially available ELISA kits. Pulmonary function tests were performed on all cases and controls using standardized protocols on SPIROLAB III. STATISTICAL ANALYSIS USED: Statistical analysis was performed using Student's t-test and Pearson's correlation coefficient. RESULTS: The levels of APN were found to be significantly higher in patients with COPD as compared to the controls and the levels increased with the severity of the disease were 16.10 ± 4.97 ng/ml and 11.43 ± 4.22 ng/ml, respectively, in AECOPD and COPD. A significant positive correlation was found between the levels of APN and interleukin (IL)-8 in patients of COPD, while the levels correlated negatively with percentage of forced expiratory volume in 1 s (FEV1%). CONCLUSIONS: The results reveal that APN is associated with the inflammatory process of COPD as suggested by its significant inverse relationship with FEV1% and positive correlation with a marker of inflammation such as IL-8. It can thus be used as a biomarker for disease severity and progression in patients of COPD, therefore aiding in risk stratification and therapeutic intervention.